Sedation and Afternoon Placement of the 48-Hour Wireless Ambulatory pH Capsule Results in More Reflux on the First Day. Issue 7 (August 2017) - Patel, Rupal; Chae, Soojong; Kumar, Ambuj; Richter, Joel E.
Abstract : Background: A 48-hour wireless capsule results often vary from the first to second day. Previous investigations comparing discrepant acid reflux readings have yielded variable results. In this study we investigated differences in data obtained on day 1 versus day 2, and the effect of time of capsule placement on discrepancies. Methods: We performed a retrospective cohort study. Patients undergoing a 48-hour wireless capsule study between January 2012 through November 2013 were eligible for inclusion. We collected reflux data for each patient and calculated the proportion of patients in four groups based on abnormal DeMeester score groups (+/+, −/+, +/−, −/−). We placed patients into morning placement or afternoon placement categories and calculated the proportions of patients with various DeMeester score discrepancies. Key Results: This study evaluated 229 patients. The mean day 1 DeMeester score was 28.38 and the mean day 2 DeMeester score was 23.24 ( P <0.0001). The mean day 1 DeMeester score in the morning group was 24.9 and 31.7 in the afternoon group ( P <0.05). The mean total DeMeester score in the morning placement group was 23.1 and 30.6 in the afternoon group ( P <0.05). Twenty-five percent of afternoon patients had a +day 1/−day 2 DeMeester discordance, whereas only 12% of morning placement patients had this discordance ( P =0.26). Conclusions: Afternoon capsule placement is associated with a significantly increased amount of acid reflux on day 1. Approximately 10% of 48-hour esophageal wireless monitoring studies may falsely overestimate reflux when the capsule is placed in the afternoon. Capsule placement should ideally be performed in the morning.